(En)countering counterfeits in Bangkok: The urban spatial interlegalities of intellectual property law, enforcement and tolerance. Issue 1 (25th April 2017) - Robinson, Daniel F.; McDuie‐Ra, Duncan
Abstract : In a Bangkok mall a fibreglass policeman warning against intellectual property (IP) piracy stands just metres away from vendors selling fake DVDs; a scene indicative of incomplete and unsuccessful attempts by foreign governments (the US and EU in particular) and corporate actors at enrolment towards ever‐higher IP standards – the "IP ratchet" that Drahos (2004 Temple Law Review, 77, pp. 401–424) describes. But the scene also reflects cultural resistance at the local level. Both readings exemplify the range of historical, cultural, and politico‐legal factors at play that can only be understood through engagement with vendors and consumers in the markets and malls of Bangkok. IP laws may achieve partial "closure" but are regularly changing, contested, variably enforced, and subject to existing social norms such as the "cult of imitation", cultures of legal informality, and a lack of social contract. We found that this lack of legal closure was most pronounced in the day‐to‐day operation of the Pratunam Market. Whilst other sites host regular crack‐downs by police, the IP‐specific DSI force, and the Thai courts, markets like Pratunam are mostly immune despite being a transnational trade node for the production and export of counterfeit garments with other developing countries, and a non‐conforming node in the IP enforcement context. In the face of persistent efforts to transpose Euro‐American IP laws in countries like Thailand, alternative and resistant nodes representing "spaces of interlegalities" are likely to persevere because of the historical context, and the socio‐cultural norms of these places.